LONG-TERM TRENDS IN FOOD CONSUMPTION: COMPARISON BETWEEN SERBIA AND GREECE - Brankov, Tatjana; Markopoulos, Theodoros; Kontakos, Stavros (Economics of Agriculture, 2019)
This study analyses the relationship between food consumption and income, taking the consumption (per capita) of different food categories and GDP (per capita) as indicators. It presents the time series trends and compares the food consumption patterns for two countries – Serbia and Greece - an upper-middle income country outside of the EU and a high-income EU member country, respectively. The analysis showed that consumption of all food groups in Serbia (except milk) over two decades (1994-2016) is significantly affected by the changes in the GDP; while in Greece, only consumption of meat, fruits, grains, and sweetened products was positive or negative influenced by GDP. Trend analysis of the consumption of the different food categories showed huge differences between the two countries.